2010
DOI: 10.1128/jb.00925-09
|View full text |Cite
|
Sign up to set email alerts
|

The Mtr Respiratory Pathway Is Essential for Reducing Flavins and Electrodes in Shewanella oneidensis

Abstract: The Mtr respiratory pathway of Shewanella oneidensis strain MR-1 is required to effectively respire both soluble and insoluble forms of oxidized iron. Flavins (riboflavin and flavin mononucleotide) recently have been shown to be excreted by MR-1 and facilitate the reduction of insoluble substrates. Other Shewanella species tested accumulated flavins in supernatants to an extent similar to that of MR-1, suggesting that flavin secretion is a general trait of the species. External flavins have been proposed to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
352
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(373 citation statements)
references
References 56 publications
17
352
4
Order By: Relevance
“…Electrodes were not reduced by MR-1 mutants that lacked MtrC. However, in cell suspension assays, MtrClacking strains reduced flavins at 50% the rate observed with the wild-type MR-1 (28). Using the proteoliposome system, we demonstrated that electrons can be transferred directly from MtrCAB to solid-phase Fe(III) oxides only when the entire MtrCAB complex is inserted.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Electrodes were not reduced by MR-1 mutants that lacked MtrC. However, in cell suspension assays, MtrClacking strains reduced flavins at 50% the rate observed with the wild-type MR-1 (28). Using the proteoliposome system, we demonstrated that electrons can be transferred directly from MtrCAB to solid-phase Fe(III) oxides only when the entire MtrCAB complex is inserted.…”
Section: Discussionmentioning
confidence: 84%
“…In vivo, bioelectrochemical experiments have shown the entire Mtr pathway is required to enable S. oneidensis MR-1 biofilms to donate electrons to and accept electrons from extracellular electrodes (28,29). Electrodes were not reduced by MR-1 mutants that lacked MtrC.…”
Section: Discussionmentioning
confidence: 99%
“…of insoluble Fe(III) oxide minerals with different electrodes, in which flavins, most notably riboflavin, play a decisive role. 9 The interaction of (alkali) metal ions with lumichrome (LC) forming a metal flavoquinone chelate, the smallest member of the flavins, can serve as a benchmark system for elucidating such processes at the molecular level. Such metal chelates are transient species in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Of the Shewanella OMMCs, the S. oneidensis MtrC and OmcA cytochromes that are the subject of the Okamato et al paper (1) have been the most widely studied. They are exported to the extracellular environment by the type II secretion system (10), and omcA mtrC mutants are severely compromised for respiratory mineral Fe(III) reduction and electron transfer to anodes in microbial fuel cells (11,12). The OmcA protein may form a 2:1 complex with MtrCAB, resulting in a system with 40 hemes that is referred to as the "OmcA-MtrCAB" complex in the paper of Okamoto et al (1).…”
mentioning
confidence: 99%